Cerâmicas ferroelétricas livres de chumbo baseadas em BaTiO3 para armazenamento de energia - Dornelas, Ramon Guilherme Flávio (2025)
In this work, barium titanate (BaTiO3) based lead-free ferroelectric ceramics were synthesized and investigated, viewing their applicability in energy-storage devices. The inclusion of the tin (Sn) ion in the perovskite structure of the BaTiO3 (BT) system has been then considered, in order to study the influence of the replacement content on the physical properties of the BaTi1–xSnxO3 (BTS) system, where x = 0.03, 0.06, 0.09, 0.12, 0.15 and 0.20). The samples were sintered from the solid-state reaction method from high-purity chemical grades. The structural Properties, investigated from X-ray diffraction and Raman spectroscopy techniques, confirmed the formation of the perovskite structure for all the cases, revealing a phases’ coexistence depending on the analyzed composition. In fact, samples in the 0.03 < x < 0.09 compositional range evidenced the coexistence between ferroelectric phases with orthorhombic and tetragonal symmetries. On the other hand, the 0.12 and 0.15 compositions revealed the coexistence of the ferroelectric and paraelectric phases, with rhombohedral and cubic symmetries, respectively, whereas the samples with x = 0.20 has shown to be a single-phase composition with the cubic paraelectric characteristic. Therefore, results reveal a strong influence of the Sn4+ cation on the structural and vibrational characteristics of the BT system. On the other hand, the dielectric properties have shown a decrease in the ferroelectric-paraelectric (high temperature) phases’ transition temperature with the increase in the tin content, whereas the low temperature ferroelectric-ferroelectric phases’ transition temperatures increased as the Sn concentration increases. Such a variation could be associated to the influence of both change and coexistence of the involved phases, with the increase of the replacement cation. The increase in the Sn concentration also promoted an enlargement in the maximum permittivity peak, indicating a diffuse-type phases’ transition promoted by cationic disorder at the B-site of the perovskite structure. Furthermore, the ferroelectric properties allowed to estimate the recovered energy as well as the storage-energy efficiency for the x = 0.15 composition (~44.98 mJ/cm² and 77 %, respectively), being both higher than the reported for other lead-free systems in the literature.